Analisis Taksonomi pada Soal Asesmen Kompetensi Minimum Literasi Membaca di SMK Negeri 3 Pekanbaru - Shafira Wardatul Aini; Muhammad Mukhlis (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
The Minimum Competency Assessment (AKM) measures literacy achievement to map the quality of education in Indonesia with international standards. This AKM aims to identify student achievements when working on AKM questions in terms of the reading literacy process. The importance of AKM training is to improve teacher skills in developing learning frameworks that lead to students' reasoning in literacy. This study aims to determine the cognitive level of reading literacy AKM at SMK Negeri 3 Pekanbaru. This research method is content analysis with a qualitative approach. The analysis uses qualitative methods to interpret the cognitive level of the items. Based on the study results, the instrument question classification I percentage was 80% for C2 (Understanding); and 20% for C4 (Analysis). The percentage of instrument II questions is 74% for C2 (Understanding), 22% for C4 (Analysis), and 3% for C6 (Create). The cognitive level dominates the lower level, namely C2 (Understanding). While cognitive levels such as C1 (Remembering), C3 (Applying), C4 (Analyzing), C5 (Creating), and C6 (Evaluating) were found to be very few and had not even appeared in the AKM Reading Literacy question at SMK Negeri 3 Pekanbaru.